(untitled) - Pember, Don R. (Boston, 2005)
This book is about censorship of the press by the government, including courts which sustain the rights of individuals in civil actions, and the topic is covered pretty thoroughly.
Keywords: Phương tiện truyền thông,Mass media,Press law; Luật và văn bản thi hành,Law and legislation; Nước Mỹ,United States,United States